Evaluating a Safe Internet Education Program to Enhance Elementary Students’ Digital Literacy in Palarahi - Hannin Pradita Nur Soulthoni; Sitti Harnia (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
The rapid increase in internet use among elementary students has not been matched by adequate digital literacy, exposing them to risks such as cyberbullying, disinformation, and misuse of personal data. This study examined the effectiveness of the Safe Internet Education Program in enhancing students’ digital literacy in Palarahi Village, Southeast Sulawesi. Using a quasi-experimental one-group pre-test and post-test design, the program was implemented through eight interactive sessions involving 85 students from two public elementary schools. The results showed a significant improvement in digital literacy scores, increasing from a mean of 52.3 to 78.6 (p < 0.001) with a large effect size (Cohen’s d = 2.31). The proportion of students in the high literacy category rose from 4.7% to 85.9%, while those in the low category dropped to 0%. The greatest improvement occurred in personal data security, followed by information evaluation and digital communication. The study concludes that structured and participatory digital education can effectively strengthen children’s competence and online safety. This model offers a measurable framework to support the implementation of the National Digital Literacy Movement (#Siberkreasi) in rural and non-metropolitan areas.